Perencanaan Desain Layout Optimal pada Unit Pelaksana Teknis Dinas Rumah Kemasan - Rottie, Ronaldo Ferdy Ignatius; Runtuwene , Eunike; Opit , Prudensy Febreine (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
UPTD Rumah Kemasan established by the Southeast Minahasa Small and Medium Enterprises Cooperative Office is a packaging service center for Small and Medium Industries (SMI), the construction of the Rumah Kemasan is based on the number of Small and Medium Industries (SMI) which has increased from year to year. The correcting problem faced by the UPTD Rumah Kemasan is related to the layout of machinery and equipment. The problem faced by the UPTD Rumah Kemasan is related to the layout of machinery and equipment. The conditions in the current areas of the Rumah Kemasan have not been determined and there is no planning and arrangement, this will certainly have a major impact on the operation of the UPTD Rumah Kemasan. There are two methods used to solve the packaging house problem, the first is BLOCPLAN (Block Layout Overview with Layout Planning) and the second is the CORELAP method (Computerized Relationship Layout Planning Algorithm) which can provide solutions related to optimal initial layout planning for the UPTD Rumah Kemasan. The results of data processing after being compared, the recommended layout is the output of the CORELAP (Computerized Relationship Layout Planning Algorithm) method, with the most optimal results, seen from several indicators and the results of the distance obtained based on the activity of the operating process map 49.2 meters and based on the distance of machines and equipment 65.78.